Evidence for Loss in Identity, De-Differentiation, and Trans-Differentiation of Islet β-Cells in Type 2 Diabetes - Hunter, Chad S.; Stein, Roland W. (Frontiers in Genetics, 2017)
The two main types of diabetes mellitus have distinct etiologies, yet a similar outcome: loss of islet -cell function that is solely responsible for the secretion of the insulin hormone to reduce elevated plasma glucose toward euglycemic levels. Type 1 diabetes (T1D) has traditionally been characterized by autoimmune-mediated -cell death leading to insulin-dependence, whereas type 2 diabetes (T2D) has hallmarks of peripheral insulin resistance, -cell dysfunction, and cell death. However, a growing body of evidence suggests that, especially during T2D, key components of -cell failure involves: 1) loss of cell identity, specifically proteins associated with mature cell function (e.g. insulin and transcription factors like MAFA, PDX1, and NKX6.1), as well as 2) de-differentiation, defined by regression to a progenitor or stem cell-like state. New technologies have allowed the field to compare islet cell characteristics from normal human donors to those under pathophysiological conditions by single cell RNA-Sequencing and through epigenetic analysis. This has revealed a remarkable level of heterogeneity among histologically defined “insulin-positive” -cells. These results not only suggest that these -cell subsets have different responses to insulin secretagogues, but that defining their unique gene expression and epigenetic modification profiles will offer opportunities to develop cellular therapeutics to enrich/maintain certain subsets for correcting pathological glucose levels. In this review, we will summarize the recent literature describing how -cell heterogeneity and plasticity may be influenced in T2D, and various possible avenues of therapeutic intervention.